2016
DOI: 10.1007/s11547-016-0655-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mammographic diagnostic errors in breast clinic

Abstract: Mammography is the gold standard for detection of early breast cancer and it is still the only diagnostic tool which shows reduction of the mortality from that. Despite that, there is a high chance of false negatives that can lead to diagnostic errors resulting in delays of treatment and worsening of prognosis. The aim of this study is to analyze the rate of false negative in mammography and assess the source of diagnostic errors. Two radiologists have retrospectively evaluated 500 mammograms performed between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…After mass ROI contouring, expertise is still needed for the classification of the identified abnormalities, which is also a challenging task for the radiologists who might be prone to misinterpretation or misdiagnosis due to factors such as inattention, fatigue or lack of experience. For example, in a blind retrospective study in diagnosing mammograms involving 250 known breast cancer patients, a 20.4% false negative rate was reported for 'expert readers' (Palazzetti et al 2016). On the other hand, similar studies showed that 60 ∼ 80% false positives were found in 5 ∼ 10% of the suspected abnormalities recommended for biopsy after follow-up mammograms (Cheng et al 2003, Hussain 2014.…”
Section: Discussionmentioning
confidence: 99%
“…After mass ROI contouring, expertise is still needed for the classification of the identified abnormalities, which is also a challenging task for the radiologists who might be prone to misinterpretation or misdiagnosis due to factors such as inattention, fatigue or lack of experience. For example, in a blind retrospective study in diagnosing mammograms involving 250 known breast cancer patients, a 20.4% false negative rate was reported for 'expert readers' (Palazzetti et al 2016). On the other hand, similar studies showed that 60 ∼ 80% false positives were found in 5 ∼ 10% of the suspected abnormalities recommended for biopsy after follow-up mammograms (Cheng et al 2003, Hussain 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of imaging models introduces subjectivity due to variations in experience, professional knowledge, and personal bias among physicians. Consequently, different healthcare professionals may yield diverse diagnostic results when analyzing the same set of images ( 12 , 13 ). Furthermore, the utilization of advanced imaging techniques such as PET-PET/CT and whole-body MRI comes with a substantial cost and potential radiation risks, leading to adverse effects on intensive follow-up programs and causing psychological distress ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Misses (i.e., false negatives) occur when malignant masses are present but not diagnosed. The miss rate in mammography is estimated at around 30–40% (Lee et al, 2013; Palazzetti et al, 2016). Alarmingly, misses have occurred at a near-constant rate of approximately 30–40% for decades (Harvey et al, 1993; Thomas & McDonald, 1969, as cited in James & Irvine, 1969).…”
mentioning
confidence: 99%